2018
DOI: 10.12659/ajcr.907494
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Liver Transplantation for Wilson’s Disease Associated with Fulminant Hepatic Failure: A Case Report

Abstract: Patient: Female, 17Final Diagnosis: Fulminant Wilson’s diseaseSymptoms: General jaundice • malaise • abdominal painMedication: —Clinical Procedure: ICUSpecialty: TransplantologyObjective:Rare diseaseBackground:Liver transplantation is indicated for patients with Wilson’s disease (WD) who present either with acute liver failure or with end-stage liver disease and severe hepatic insufficiency as the first sign of disease. However, almost all reported cases have been treated with death donor liver transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…A Case of LDLT for WD-Induced ALF in Japan [20] Authors report the case of a patient with WD associated with fulminant hepatic failure (WD-FHF) who underwent LDLT. A 17-year-old female was diagnosed with WD-FHF based on high uric copper (10,603 μg/day, normal <100 μg/day), low serum ceruloplasmin (15 mg/dL, normal >20 mg/dL) and Kayser-Fleischer corneal ring, and ALF, acute renal failure and grade 2 hepatic encephalopathy.…”
Section: Annals Of Liver Transplantation Annals Of Liver Transplantationmentioning
confidence: 99%
“…A Case of LDLT for WD-Induced ALF in Japan [20] Authors report the case of a patient with WD associated with fulminant hepatic failure (WD-FHF) who underwent LDLT. A 17-year-old female was diagnosed with WD-FHF based on high uric copper (10,603 μg/day, normal <100 μg/day), low serum ceruloplasmin (15 mg/dL, normal >20 mg/dL) and Kayser-Fleischer corneal ring, and ALF, acute renal failure and grade 2 hepatic encephalopathy.…”
Section: Annals Of Liver Transplantation Annals Of Liver Transplantationmentioning
confidence: 99%
“…Published experience, predominantly from Asian populations, has shown that transplants using heterozygous donors are safe with complete functional correction of the defect (7)(8)(9)(10)(11)(12)(13)(14)(15). Heterozygotes for WD gene have abnormal ceruloplasmin levels in almost 25% of subjects, most of whom have normal urinary copper excretion (11).…”
Section: Wilson Diseasementioning
confidence: 99%
“…WD is an autosomal‐recessive disease characterized by copper buildup in the liver and other end organs . Patients can present with neurologic symptoms, chronic liver disease, or ALF . Fulminant WD represents about 3% of ALF cases and usually occurs in young female patients within the first 2 decades of life .…”
Section: Epidemiology and Etiologymentioning
confidence: 99%